Before the Revolution : America's ancient pasts - Richter, Daniel K. (Belknap Press of Harvard University Press, 2011)
This work is an investigation of North American history in the seven centuries before the founding of the United States, looking at how the sequential cultural layers defined by people the author calls the progenitors, conquistadores, traders, planters, imperialists, and Atlanteans contributed to the society, culture, and politics of the U.S. as it emerged after the Revolutionary War. It includes sections on Albany, New York; Boston, Massachusetts; Charleston, South Carolina; corn; fur trade; Florida; Jamestown, Virginia; Maryland; Massachusetts Bay Colony; New York City; Philadelphia, Pennsylvania; Rhode Island; St. Augustine, Florida; and Virginia.